Scleroderma Renal Crisis Associated With Microangiopathic Hemolytic Anemia in a Patient With Seronegative Scleroderma and Monoclonal Gammopathy - Mark Riley DO; Paul Der Mesropian DO; Ana Maheshwari MBBS; Mustafa Erdem Arslan MD; Parth Visrodia MD; Loay Salman MD; Ruben Peredo-Wende MD; Llewellyn Foulke MD; Krishnakumar Hongalgi MD (SAGE Publishing, 2022)
Systemic sclerosis with negative serology, particularly that complicated by scleroderma renal crisis (SRC), is rarely encountered. We describe a patient with seronegative systemic sclerosis who developed acute kidney injury, proteinuria, and hypertensive emergency following motor vehicle-related trauma and in the setting of nonsteroidal anti-inflammatory drug use. Findings on physical examination, imaging, and skin biopsy led to a clinical diagnosis of scleroderma, despite the lack of supportive laboratory data. IgG lambda paraproteinemia was detected on workup. Bone marrow biopsy showed plasmacytosis and trace lambda-restricted plasma cells consistent with monoclonal gammopathy of undetermined significance. Chemotherapy was initially started given concern for myeloma with cast nephropathy but was later stopped after a kidney biopsy revealed thrombotic microangiopathy (TMA). The SRC associated with TMA was ultimately diagnosed, though atypical hemolytic uremic syndrome (aHUS) induced perhaps by monoclonal gammopathy or hypertension was also possible. Captopril and eculizumab were initiated for SRC and aHUS, respectively. Despite therapy, renal function did not recover, and the patient required hemodialysis indefinitely. This case highlights clinical features common to both SRC and aHUS as well as points out a few ways to differentiate between them.